Klakson: Innovation in the Development of a Barber Johnson Charting Calculator Based on an Early Warning System (EWS) - Ningsih, Kori Puspita; Purbobinuko, Zakharias Kurnia; Pradipta, Dimas Andrenawan; Farhan, Ishlah Maulana; Rohmah, Kuny Lutfiyatur (Procedia of Engineering and Life Science, 2024)
Data on bed management in Indonesia is currently managed in an integrated manner by the Ministry of Health through the Integrated Referral System (SISRUTE) on the Satu Sehat website. Hospital bed management data can be presented in the Barber-Johnson Graph. The Barber Johnsons graph is a good tool. It makes it easier for managers to monitor the efficiency of bed use, because TOI (Turn Over Interval), LOS (Length Of Stay), BTO (Bed Turn Over), and BOR (Bed Occupation Rate) are presented in one graph. The problem currently faced by society is that the management of beds in healthcare facilities is not yet efficient and is still done manually. In some hospitals, they still describe the Barber-Johnson Chart in Microsoft Excel. Therefore, innovation is needed to develop the Barber-Johnson Graph Calculator application Johnson is based on an Early Warning System (EWS) called Klakson. The existence of efficient bed management will demonstrate quality service. This is certainly expected to impact improving public health in Indonesia. This research uses action research, with a qualitative data collection approach. Data analysis uses content analysis. The results of need identification show that hospitals, health centers, and clinics that provide inpatient care need a Klakson application based on the Early Warning System (EWS) in the form of notifications and sound to support early decisions. The results of the feasibility study show that users are accustomed to using computers, software, and hardware available to support the development of web-based information systems. Information system development using prototype methodology. The prototype test results using the Blackbock method show that the function/reaction is according to the actor, the system works well and can meet user needs. The development of the web-based Klakson application using prototype methodology stages has been tested in DIY clinics and shows that the system can meet user needs.